Roseoside Is a Bioactive Compound in Kirengeshoma koreana Nakai Extract with Potent In Vitro Antiviral Activity Against Hepatitis C Virus - Jun-Kyu Lee; Ji-Wan Choi; InWha Park; Na-Eun Kim; Hak Cheol Kwon; Jaeyoung Kwon; Yoon-Jae Song (Molecules)
Hepatitis C virus (HCV) is a pathogen that causes cirrhosis and hepatocellular carcinoma through chronic hepatitis C. This study focused on the anti-HCV activity of a 70% ethanol extract of Kirengeshoma koreana Nakai (KKE) and its bioactive chemical constituent(s). The KKE and its n-butanol (n-BuOH) fraction induced a significant reduction in HCV RNA levels without inducing cytotoxicity. A high-performance liquid chromatography–mass spectrometry (HPLC-MS) analysis revealed the presence of roseoside in the n-butanol fraction of the KKE, which inhibited HCV RNA replication in a concentration- and time-dependent manner without exerting cytotoxicity. Consistent with in silico molecular docking analysis data, roseoside targets and inhibits HCV NS5A/B replicase. Collectively, our findings demonstrate that roseoside is a chemical constituent in KKE that interferes with HCV replication by targeting NS5A/B replicase.